Governança corporativa,desempenho,valor e risco: estudo das mudanças em momentos de crise - Fernanda Maciel Peixoto (2012)
This research aimed to examine the relationship between corporate governance and performance/value/risk of publicly traded Brazilian companies in periods of crisis and noncrisis. The time span investigated involved the period from 2000 to 2009, segmenting it into three sub-periods: moderate crisis (2000-2002), non-crisis (2003-2007) and deep crisis (2008- 2009). The definition of the years of crisis and non-crisis was based on the literature on the subject and in the evolution of the Bovespa Index and the Brazilian GDP. The study of performance, value and risk of the companies during periods of crisis allows us to understand some aspects of corporate governance that are less evident during normal economic situations. In periods of economic growth, investors tend to ignore the lack of good corporate governance. But when a crisis starts and expected returns fall substantially, investors begin totake into account governance weaknesses, especially in countries where minority shareholder rights are not well protected. The chosen governance mechanisms were: control and ownership structure, board of directors, management compensation, transparency of publishedinformation, and protection of minority shareholders. Such mechanisms have been aggregated into an index of quality of governance using the method of principal components analysis. Afterwards, the panel data regression was used to investigate the relationship between theindex of governance quality and aspects of performance/value/risk in the Brazilian context. The following indicators were used: (i) for performance: net margin, ROA, ROE, EBITDA/Total Assets and EBIT/Sales; (ii) for market value: Tobin's Q, market-to-book related to total assets, market-to-book related to equity and the risk adjusted rate of return;(iii) for risk: beta and weighted average cost of capital. Regarding the performance, the accounting ratios mencioned above were aggregated into an index of accounting performance using principal component analysis. In a third stage, the Chow test was used to verify whetherstructural breaks occurred on certain points of the regression line. As a result, it was found that the ownership structure and control mechanism was less relevant throughout the analyzed period, and presented a reduction of its importance in times of non-crisis and deep crisis. Intimes of moderate crisis, the most important dimension of governance was the management compensation. In periods of non-crisis and deep crisis, the most important governance mechanism was the protection of minority shareholders. The transparency of the published information showed less importance throughout the years of the study. During the period analyzed, the mechanisms related to the board of directors grew in relevance, although having shown less importance than the management compensation and protection of minority shareholders. Furthermore, regarding the main relationships investigated, it was found that the accounting performance and risk measures showed no significant relationship with the index of governance quality, with exception for the beta in some specifications. Considering the measures of value, it was found that well-governed companies have higher market value at the period of deep crisis (2008-2009), and that investors demand a lower risk adjusted rate of return from well-governed firms during the U.S. subprime crisis, even though this was not observed in the total sample period of this investigation.